Potential of Rambutan-Honey Antioxidants in Reducing Malondialdehyde Levels and Regenerating Hepatocyte Cells in Isoniazid-Rats Induced - Yuslianti, Euis Reni; Ratwita, Welly; Koswara, Teja; Afra, Aldilla (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Hepatotoxicity induced by prolonged administration of antituberculosis drugs such as isoniazid (INH) is associated with the production of free radicals. Rambutan-honey, rich in catalase enzyme, flavonoids, and vitamin C, exhibits antioxidant and immunomodulatory properties. This study purpose to assess the effect of rambutan-honey on malondialdehyde (MDA) levels and hepatocyte cell numbers in INH-induced rats. The research method using in vivo experimental study with a randomized posttest-only control group design. Thirty Wistar rats were divided into five groups: negative control(G1), positive control(G2), and three groups treated with rambutan-honey at doses of 250 mg/kgBW(G3), 500 mg/kgBW(G4), and 1000 mg/kgBW(G5). MDA levels were measured using the TBARS method on days 15 and 23, while hepatocyte cell numbers were assessed through histopathological examination using Hematoxylin-Eosin. Data were analyzed using One-Way ANOVA followed by Post-Hoc test. This study revealed that rambutan-honey at doses of 250, 500, and 1000 mg/kgBW significantly reduced MDA levels compared to controls, with a simultaneous increase in hepatocyte cell numbers (p=0.001). The conclusion of this research is the potential of rambutan-honey as an antioxidant and hepatoprotective agent, possibly mediated by its flavonoid content, which may stimulate superoxide dismutase activity akin to catalase enzyme and vitamin C.